2020
DOI: 10.1017/s1368980020004541
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of disability-adjusted life years for diseases due to low fruit intake in 2017–2040 in Japan

Abstract: Objective This study aimed to predict disability-adjusted life years (DALYs) rate in Japan through 2040 with plausible future scenarios of fruit intake for neoplasms, cardiovascular diseases (CVDs), and diabetes and kidney diseases (DKDs). Design Data from National Health and Nutrition Surveys and the Global Burden of Diseases study in 2017 were used. We developed an autoregressive integrated moving average model with four future scenarios. Reference scenario maintains the current trend.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
(34 reference statements)
0
5
0
Order By: Relevance
“…This reflects the Japanese lifestyle of eating watermelon in summer and mandarin oranges and apples in winter, while bananas and kiwis are eaten all year around. Also, in Japan, elderly people are reported to consume more fruit and vegetable than younger people [25]. Although it has been reported that the intake of fruits and green and yellow vegetable are higher in summer than in winter, the potassium content of fruits and vegetables varies widely from food to food and these factors need to be taken into account when considering the effect on serum potassium levels [26].…”
Section: Discussionmentioning
confidence: 99%
“…This reflects the Japanese lifestyle of eating watermelon in summer and mandarin oranges and apples in winter, while bananas and kiwis are eaten all year around. Also, in Japan, elderly people are reported to consume more fruit and vegetable than younger people [25]. Although it has been reported that the intake of fruits and green and yellow vegetable are higher in summer than in winter, the potassium content of fruits and vegetables varies widely from food to food and these factors need to be taken into account when considering the effect on serum potassium levels [26].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, we found that the percentage of people who meet the dietary goal for seven essential nutrients-designed to reduce the risk of lifestyle-related chronic diseases in Japan's 2015 national nutrient-based dietary guideline-was only 0.3% in 2017 [8]. We have also identified remarkable differences in disease burden between the scenarios, representing a wide scope of future trajectories of food intake with the potential for a tremendous decrease in the burden by 2040 [9] [10]. While it is important to note that foods are more than just a collection of nutrients and that focusing on individual nutrients does not necessarily translate to a healthy diet [11], there is room for Japan to improve its diet to maintain and further develop its population's health.…”
Section: Japanese Diet and Dietary Risksmentioning
confidence: 95%
“…Metabolic risk is also contributing to a large number of deaths, with high systolic blood pressure accounting for 196,385 deaths in 2019 (Figure 3), followed by high fasting plasma glucose (causing 100,809 deaths), kidney dysfunction (78,418), high LDL cholesterol (75,782), and high BMI (51,822). In addition to these five metabolic factors, the top 10 risk factors for deaths from NCDs in 2019 included tobacco smoking (causing 187,238 deaths), Helicobacter pylori infection (49,284), alcohol use (41,554), high-sodium diets (38,087), and diets low in whole grains (30,877). Metabolic risk factors collectively accounted for 24.64% of the total number of deaths from NCDs in 2019, which has slightly increased since 2013 (24.22%).…”
Section: Increase In Risk Factors Contributing To Ncdsmentioning
confidence: 99%
“…Several previous studies have forecasted future changes in health loss in DALYs in Japan to which dietary risk factors contribute, including high salt intake, under various future intake scenarios. 48 , 49 , 50 Significant gaps in the estimates of future health loss between scenarios were identified, indicating that future policies targeting risk factors in a population may have a significant impact on future trajectories of risk factor profiles in Japan and associated health losses.…”
Section: More Public Health Efforts Are Needed To Address Critical Ri...mentioning
confidence: 99%